Structure of cylindrical electric double layers: Comparison of density functional and modified Poisson-Boltzmann theories with Monte Carlo simulations - Dorvilien, V.; Patra, Ch.N.; Bhuiyan, L.B.; Outhwaite, Ch.W. (Condensed Matter Physics, 2013)
The structure of cylindrical double layers is studied using a modified Poisson Boltzmann theory and the density functional approach. In the model double layer the electrode is a cylindrical polyion that is infinitely long, impenetrable, and uniformly charged. The polyion is immersed in a sea of equi-sized rigid ions embedded in a dielectric continuum. An in-depth comparison of the theoretically predicted zeta potentials, the mean electrostatic potentials, and the electrode-ion singlet density distributions is made with the corresponding Monte Carlo simulation data. The theories are seen to be consistent in their predictions that include variations in ionic diameters, electrolyte concentrations, and electrode surface charge densities, and are also able to reproduce well some new and existing Monte Carlo results.